Development of novel ultrafine grain Cu metal matrix composites reinforced with Ti-Cu-Co-M (M: Ni, Zr) amorphous-nanocrystalline powder - Janovszky, Dora; Kristaly, Ferenc; Miko, Tamas; Sveda, Maria; Sycheva, Anna (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
Novel ultrafine grain composites of Cu matrix reinforced with 2-50 wt. % of Ti48Cu39.5Ni10Co2.5 and Ti48Cu39.5Zr10Co2.5 (at. %) amorphous-nanocrystalline alloy particles have been fabricated by powder metallurgy. The composites showed a homogeneous structure. The characterization of composites was performed by optical and scanning electron microscopy (SEM), X-ray powder diffraction (XRD), micro- and macrohardness, as well as density measurements. After hot-pressing the crystallite size of Cu was smaller than 200 nm and nanocrystalline phases of reinforcing powder were 5-35 nm. Densities of 97-76 % relative to calculated values of consolidated composites were obtained, depending on the reinforcing weight fraction. Additionally, the mechanical properties and electrical resistivity of composites have been investigated. The results reveal that the 0.2% offset compressive yield strength of composites increases by two and five times, with respect to pure Cu matrix, for the composites reinforced with 2 and 50 wt. % of reinforcing particles, respectively. Electrical resistivity increases continuously, with higher values after 30 wt. % of addition. Changes in mechanical and electrical properties were produced by the increase of amorphous-nanocrystalline additive.